Advances in molecular and cell therapy for immunotherapy of cholangiocarcinoma - Zhao, Li-ming; Shi, An-da; Yang, Yan; Liu, Zeng-li; Hu, Xiao-Qiang; Shu, Li-Zhuang; Tang, Yong-chang; Zhang, Zong-li (Frontiers in Oncology, 2023)
Cholangiocarcinoma (CCA) is a highly malignant tumor of the hepatobiliary system that has failed to respond to many traditional therapies to a certain extent, including surgery, chemotherapy and radiotherapy. In recent years, the new therapeutic schemes based on immunology have fundamentally changed the systemic treatment of various malignant tumors to a certain extent. In view of the immunogenicity of CCA, during the occurrence and development of CCA, some immunosuppressive substances are released from cells and immunosuppressive microenvironment is formed to promote the escape immune response of its own cells, thus enhancing the malignancy of the tumor and reducing the sensitivity of the tumor to drugs. Some immunotherapy regimens for cholangiocarcinoma have produced good clinical effects. Immunotherapy has more precise characteristics and less adverse reactions compared with traditional treatment approaches. However, due to the unique immune characteristics of CCA, some patients with CCA may not benefit in the long term or not benefit at all after current immunotherapy. At present, the immunotherapy of CCA that have been clinically studied mainly include molecular therapy and cell therapy. In this article, we generalized and summarized the current status of immunotherapy strategies including molecular therapy and cell therapy in CCA in clinical studies, and we outlined our understanding of how to enhance the clinical application of these immunotherapy strategies.